Ferramentas de ensino na conceituação da nanotecnologia na educação básica - Evangelista, Lucas Vairolette (2023)
TEACHING TOOLS IN THE CONCEPT OF NANOTECHNOLOGY IN BASIC EDUCATION. Nanotechnology has a high impact on people's quality of life, being present in the development of clean energy, more efficient mobile devices, the treatment of diseases, the production of prosthetics, cosmetics, pharmaceuticals, among others. However, the clarity and understanding with which this topic has been discussed in the media is questioned, so the aim is to clarify whether this knowledge is being announced to students in a way that is dissociated from their reality. It is also clear that despite the large amount of information available, quality is sometimes lacking in its preparation, failing to highlight fundamental points, such as its definition, impacts and relevance for the development of society. Therefore, through this work, it is proposed to apply a didactic sequence to a class of high school students from a public school in São Paulo, in order to verify their level of knowledge and familiarity with the topic of N&N, and also, teach basic and fundamental concepts regarding nanometric materials, their benefits and risks, advantages and disadvantages of their applications, seeking to encourage the development of a critical opinion based on scientific knowledge. To achieve this, this sequence was carried out in four classes, the first being a diagnostic assessment and debate, the second a demonstrative experimental practice, the third constitutes a presentation of student seminars on N&N applications, and the fourth was a final questionnaire on the content covered in the classes taught. It was concluded that students' knowledge about nanotechnology and nanoscience is still superficial, despite the profusion of currently existing technological applications and their dissemination in the media. Furthermore, there is a lack of cohesion in the writing and interpretation of texts in their responses and there is great difficulty in assimilating associated chemical concepts, so that a greater focus in future work on reading and the development of formal and chemical writing is suggested.